Diabetes and technology: A pilot study on the management of patients with insulin pumps during the COVID-19 pandemic. (November 2020) - Petrelli, Fabio; Cangelosi, Giovanni; Scuri, Stefania; Pantanetti, Paola; Lavorgna, Francesca; Faldetta, Federica; De Carolis, Cristina; Rocchi, Renato; Debernardi, Giulia; Florescu, Alexandra; Nittari, Giulio; Sagaro, Getu Gamo; et al.
Abstract: Background: The recent COVID-19 pandemic has accelerated the treatment process through IT/technological supports, useful in the management of chronic patients such as those affected by type 1 Diabetes Mellitus (T1DM). Specific routes for fragile patients such as those with micro-infusers have been created thanks to the application of "Diabetes Technology, " which allows patients to monitor blood glucose quickly and easily. The present pilot study aimed to assess the quality of care provided to patients with micro-infusers in a delicate phase such as a pandemic lockdown. Materials and methods: A mixed-methods approach was used. In the first part, with prior written consent, patients with insulin pumps enrolled voluntarily. In the second part, the focus group discussion (FGD) was carried out with the voluntarily enrolled participants. The FGD data were organized and analyzed by the thematic areas. Results: The number of patients with afferent insulin pumps at the center was 50 individuals. Among them, 20 patients voluntarily joined the first part of the study by completing the PACIC questionnaire, which gave an average result of 3.34 (min. 2.2 and max. 4.2). In the second part, the application of the focus group technique demonstrated that technology is decisive in the management of diabetic pathology, not only in the emergency phase. Conclusions: At the time of public health crises, alternative strategies such as Tele-Nursing or Telemedicine could be crucial for the management of patients with micro-infuser not only in critical moments, such as lockdown, but also in ordinary health management.